International comparison of generic competition, prices, and usage trends: South Korea and G20 countries - Lee, Da Hye; Kim, Jung-Ae; Lim, Kyung Min; Jung, Ji Won; Park, Su Min; Jang, Yoon-A; Lee, Jong Hyuk (Frontiers in Public Health, 2025)
IntroductionWhile many countries have successfully promoted generic drug use, South Korea faces challenges with low utilization and high expenditure shares, despite various policy reforms. This study aimed to evaluate the effectiveness of generic drug policies in South Korea, by comparing the prices, competition, and usage trends of generic drugs between South Korea and the Group of Twenty (G20) countries.MethodsWe analyzed 26 off-patent active ingredients marketed in South Korea and G20 countries from 2014 to 2023. Generic drug prices were calculated by dividing total sales by total volume in 2023, with the average price for each country subsequently determined. Generic competition was measured by the number of generic drugs available in each country. The usage trends of generic drugs were assessed using the sales and volume ratios of off-patent original drugs to generic drugs in 2023.ResultsSouth Korea had more generic drugs for 19 of the 26 analyzed ingredients (73.1%) compared to other G20 countries. However, for recently off-patent ingredients, the number of generic drugs was smaller in South Korea. The generic prices for 18 ingredients (69.2%) were lower in South Korea than in the G20 and Advanced Eight (A8) countries. Similar to the generic competition, generics with larger market sizes had higher prices in South Korea. Conversely, the prices of recently off-patent ingredients were higher in South Korea compared to the G20 countries. For 24 ingredients (92.3%), the sales and volume ratios of generic drugs in South Korea were considerably lower compared to the G20 countries.ConclusionThis study confirms that the pharmaceutical policies and regulatory frameworks for generic drug are fragmented and inefficient in South Korea. Consequently, these fragmented and inefficient policies disrupt the virtuous cycle mechanism of generic price and usage driven by effective competition. To address these challenges and promote the use of generic drugs, the findings of this study suggest the need to develop and implement policies in South Korea that focus on optimizing the pharmaceutical expenditure structure, enhancing post-listing price management system for generic drugs, supporting the accelerated development of generic drugs, and promoting the prescription and use of generic drugs.